Electron-Beam Irradiated Recombinant Human Collagen-Phosphorylcholine Corneal Implants Retain Pro-Regeneration Capacity - Simpson, Fiona C.; Islam, Mohammed Mirazul; Buznyk, Oleksiy; Edin, Elle; Groleau, Marc; Kozak-Ljunggren, Monika; Magrelli, Federica M.; AbuSamra, Dina B.; Argüeso, Pablo; Chodosh, James; Liszka, Aneta; Fagerholm, Per; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Sterilization of biodegradable, collagen-based implants is challenging as irradiation sterilization methods can alter their mechanical properties. Electron beam (EB) irradiation is a terminal sterilization method that has been used for biologically-derived implants. Here, recombinant human collagen and type III-phosphorylcholine (RHCIII-MPC) hydrogels were irradiated with EB doses of 17 kGy, 19 kGy, or 21 kGy and their subsequent biocompatibility and ability to promote regeneration in rabbit corneas was evaluated. Unirradiated hydrogels stored in 1% chloroform in phosphate-buffered saline (C-PBS) were the controls. There were no significant differences between irradiated and non-irradiated samples in optical or physical properties (tensile strength, modulus, elasticity), or the ability to support cell growth. However, irradiated implants were more sensitive to high levels of collagenase than unirradiated controls and the C-PBS implants had increased cell growth compared to EB and controls at 72 hours. Corneal implants e-beamed at 17 kGy or e-beamed and subsequently frozen to increase shelf-life showed no adverse biological effects of the irradiation. EB, EB-F, and C-PBS implanted corneas all rapidly re-epithelialized but showed mild neovascularization that resolved over six months. The regenerated neo-corneas were transparent at six months post-operation. In vivo confocal microscopy confirmed normal morphology for the epithelium, stroma, sub-basal nerves and unoperated endothelium. Histology showed that all the regenerated corneas were morphologically similar to the normal. Immunohistochemistry indicated the presence of a differentiated corneal epithelium and functional tear film. In conclusion, the e-beamed corneal implants performed as well as non-irradiated control implants, resulting in fully regenerated neo-corneas with new nerves and without blood vessels or inflammation that may impede vision or corneal function. Therefore, a complete validation study to establish EB irradiation as an effective means for corneal implant sterilization prior to clinical application is necessary as a next step.